Weak Firms Follow Strong Firms in Hot IPO Markets. (26th February 2013) - Chang, Kiyoung; Kim, Yong‐Cheol; Shim, Hyeongsop
Abstract We investigate whether initial public offerings (IPO) occurring during hot markets are fundamentally different from those occurring during cold markets. Firms that go public during hot markets show lower survival probability, shorter survival duration, and worse long‐run performance. When hot markets are separated into two periods, we find early issuers during hot markets (pioneers) have better investment opportunities than late issuers during the same hot markets (followers). Furthermore, pioneers show higher survival probability, longer survival duration, and better long‐run performance than followers. Our evidence shows that the inferior quality of followers is a major contributor to the difference between hot and cold IPO markets.